If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(4x-5)+2=2x-32
We move all terms to the left:
4(4x-5)+2-(2x-32)=0
We multiply parentheses
16x-(2x-32)-20+2=0
We get rid of parentheses
16x-2x+32-20+2=0
We add all the numbers together, and all the variables
14x+14=0
We move all terms containing x to the left, all other terms to the right
14x=-14
x=-14/14
x=-1
| 5x-6=4(2x-3) | | 5x-11=3(3x+3) | | -2x+36=2(2x+3) | | 4(x-4)=3x-17 | | 3(x-3)+4=5x-1 | | 3x+44=2(5x+1) | | -23=3(x-5)+10 | | 1=-4.9x^2+21x+1.2 | | 5(x-4)=-x+34 | | 9x+28=2x+84 | | Y=-4.9x^2+21x+0.2 | | 2x+20=-x+23 | | 0=5/4(x-6/5 | | 7x-17=5x+3 | | 3(2-3x)=7(x+1)-33 | | 12-2=3x-6 | | 10r−-7r−20r−17r=-20 | | 3.47(2x-4)+9.773x+1.004=5.216-(x-7.112) | | 12x^2(4x-3)=0 | | 2t=8+1/2t-t=11 | | 2r+24/8=2r-18/2 | | x=3/x+2 | | 4/x-4=x | | -7=5(x+2)+8 | | -4x-36=4(3x+3) | | x-25=3(2x-5) | | -9x-9=-3x-63 | | -x-49=2(2x+3) | | x-28=5(4x+2) | | 4(3x-5)-1=-x+5 | | 5x+27=2(x+5)-10 | | 26=2(3x+4) |